Genetic factors contributing to hereditary cardiovascular disorders - Anand Das Vaishnav, Venu; Patel, Ritesh (Journal of Neonatal Surgery, 2025)
Hereditary cardiovascular disorders (HCDs) represent a group of conditions with a significant genetic component, contributing to the development of various heart-related diseases. These disorders are influenced by mutations in specific genes that affect cardiac structure, function, and susceptibility to cardiovascular events. Hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), congenital heart defects, and arrhythmogenic right ventricular cardiomyopathy (ARVC) are some of the prominent HCDs linked to genetic factors. Recent advancements in genomic technologies, such as whole-exome sequencing (WES) and next-generation sequencing (NGS), have facilitated the identification of pathogenic variants and their role in disease pathology. These technologies have not only improved the accuracy of genetic diagnosis but have also enabled the development of precision medicine strategies tailored to individual genetic profiles. Additionally, gene editing tools, such as CRISPR/Cas9, are being explored for potential therapeutic applications, offering hope for correcting specific genetic mutations responsible for HCDs. This study reviews the current understanding of genetic factors contributing to HCDs, explores novel diagnostic and therapeutic approaches, and discusses the challenges associated with translating genetic findings into clinical practice.